The awareness of the risk for urinary incontinence among pregnancy women in Hospital Universitl Sains Malaysia (HUSM) - Abdullah, Che Siti Nurzaily (Universiti Sains Malaysia, 2012)
Urinary incontinence (UI) is a major health problem among adult, especially for women. Even though Urinary incontinence had been established by worldwide long time ago, the problem is still less approach and lack of knowledge among the caregiver and the individuals experience UI especially among the pregnant women. The aim of this study is to determine awareness of the risk for UI among pregnancy women. Samples was taken by randomly sampling among pregnant women, being the first pregnancy and attending antenatal clinic in HUSM (n=100). A constructed questionnaire was used to collect data. The participants comprised of 84% younger adult (less than 30 years old) and the rest is 30 years old and above. The finding shows that the awareness related to risk for UI was less among pregnancy women. There was a significant association between educational level, family income, experiencing of UI, knowing the treatment, knowing about UI and had been asked by health professional with awareness of the risk for UI. The result also shows no significance association with age, gestational age and being employed. In conclusion, improvement to the practiced management of UI is till need to be done in order to increase awareness of this common health problem. So, the scope of health professional’s responsibility need to be broad in giving health education to the public about the seriousness of the problem and it impact to individual’s life.